Ultrasound-guided antecubital vein approach for right heart catheterisation in a Brazilian tertiary centre. Issue 1 (4th February 2020) - Valle, Felipe Homem; Wainstein, Rodrigo Vugman; Matte, Bruno Silva; Gonçalves, Sandro Cadaval; Bergoli, Luiz Carlos C; Krepsky, Ana Maria Rocha; Pivatto Junior, Fernando; de Araujo, Gustavo Neves; Machado, Guilherme Pinheiro; Wainstein, Marco Vugman
Abstract : Objective: As a parallel to the radial approach for left heart catheterisation, forearm veins may be considered for the performance of right heart catheterisation. However, data regarding the application of this technique under ultrasound guidance are scarce. The current study aims to demonstrate the feasibility of right heart catheterisation through ultrasound-guided antecubital venous approach in the highly heterogeneous population usually referred for right heart catheterisation. Methods: Data from consecutive right heart catheterisations performed at an academic centre in Brazil, between January 2016 and March 2017 were prospectively collected. Results: Among 152 performed right heart catheterisations, ultrasound-guided antecubital venous approach was attempted in 127 (84%) cases and it was made feasible in 92.1% of those. Yet, there was no immediate vascular complication with the antecubital venous approach in this prospective series. Conclusions: Ultrasound-guided antecubital venous approach for the performance of right heart catheterisation was feasible in the vast majority of cases in our study, without occurrence of vascular complications.